Legal Analysis of Criminal Punishment for Perpetrators of Illegal Mining Criminal Acts Resulting in Forest Damage (Decision Number 495/Pid.Sus/2022/PN Kdi) - Nola Putra E. C Simanungkalit; Martono Anggusti; July Esther (Journal of Law, Politic and Humanities, 2025)
This research focuses on the analysis of forest damage due to mining activities carried out without permits, which is considered a criminal act. Apart from that, this research also discusses criminal liability and the judge's considerations in imposing penalties related to forest damage caused by illegal mining based on Decision Number: 495/Pid.Sus/2022/PN Kdi. The approach used in this research is normative, involving a statutory approach, conceptual approach, and case approach, as well as utilizing primary and secondary legal sources from literature studies, with prescriptive analysis. From this research, several conclusions were found. Firstly, mining carried out without a permit in the forest is classified as a criminal act of illegal mining which is regulated in Law Number 3 of 2020 which amends Law Number 4 of 2009 concerning Mineral and Coal Mining, especially relating to the management of forest areas without permits as stated in listed in Article 78 paragraph (2) letter , in conjunction with Article 50 paragraph (3) letter a, of Law Number 41 of 1999 concerning Forestry. Second, for criminal liability resulting from misuse of mining business permits which causes forest damage, the sanctions imposed are in the form of prison sentences and fines, which can result in imprisonment for six months and a fine of Rp. 500,000,000.00. If the fine is not paid, it will be replaced by a prison sentence of two months. This is due to the fact that the defendant was legally and convincingly proven to be involved in the act of "taking part in carrying out, using and occupying forest areas illegally".